A Novel Densovirus Isolated From the Asian Tiger Mosquito Displays Varied Pathogenicity Depending on Its Host Species - Li, Jing; Dong, Yunqiao; Sun, Yan; Lai, Zetian; Zhao, Yijie; Liu, Peiwen; Gao, Yonghui; Chen, Xiaoguang; Gu, Jinbao (Frontiers in Microbiology, 2019)
Mosquito-borne viral diseases (MBVDs) continue to pose a significant global public health burden. Mosquito control remains a core intervention strategy in integrated mosquito management (IMM) programs to reduce the transmission of MBVDs. Mosquito densoviruses (MDVs) are mosquito-specific entomopathogenic viruses, and their attractive biological and pathogenic characteristics make MDVs potential biological control agents as alternatives to traditional chemical pesticides. However, different viral strains vary greatly in their pathogenicity against different mosquito species, which poses an obstacle for the wide application of MDVs in vector control. In this study, a novel MDV, Aedes albopictus densovirus-7 (AalDV-7), was isolated from field-collected Aedes albopictus in the dengue-endemic area of Guangzhou, China. The complete 4,048 nt genome of AalDV-7 was cloned and sequenced, and the transcription and translation of three open reading frames (ORFs) were characterized. Phylogenetic analysis indicated that AalDV-7 clustered with MDVs mostly isolated from indigenous mosquitoes. The pathogenicity of AalDV-7 to A. albopictus, Aedes aegypti, and Culex quinquefasciatus larvae was completely different, and the median lethal dose (LD50) of AalDV-7 in A. albopictus which was 109.48 genome equivalents per ml (geq/ml) was 12 and 46 times lower than those in A. aegypti (1010.56 geq/ml) and C. quinquefasciatus (1011.15 geq/ml). Furthermore, the median lethal time (LT50) value in A. albopictus (7.72 days) was 25% and 26% shorter than those in A. aegypti (10.24 days) and C. quinquefasciatus (10.42 days) at a titer of 1011 geq/ml. Furthermore, the mortality of AalDV-7-infected mosquitoes increased in a dose-dependent manner, and the highest mortality was found in A. albopictus larvae exposed to 1011 geq/ml AalDV-7 (82.00%). Sublethal effects analysis also showed that AalDV-7 infection significantly decreased pupation and emergence rates. The 1st–2nd instar larvae of all three mosquito species showed a near 100% infection rate, and the highest relative vial titer (305.97 ± 67.57 geq/ng) was observed in the 1st–2nd instar larvae of C. quinquefasciatus. These pathogenic characteristics make AalDV-7 a potential MBVDs control agent in China, whereas its negligible pathogenicity and high infection rate and viral dose in vivo make it a good candidate for gene delivery vectors in C. quinquefasciatus gene function analysis. In conclusion, the continuous discovery and isolation of new MDVs enrich the pool of mosquito entomopathogenic viruses and provide a variety of choices for optimal MDVs or combinations of MDVs to target certain mosquitoes.